Sārānukrom klum chātphan K̨ōng (ʻUk̨ōng) - Mayurī Thāw̨ōnphat (Sathāban Wičhai Phāsā læ Watthanatham ph̄ưa Phatthanā Chonnabot, Mahāwitthayālai Mahidon, 1997)
Commemorative volume brought out at 50th anniversary of enthronement of Bhumibol Adulyadej, King of Thailand, b. 1927.